THE ROLE OF LIGNITE IN THE CARBON CYCLE OF LIGNITE-CONTAINING MINE SOILS: EVIDENCE FROM CARBON MINERALISATION AND HUMIC ACID EXTRACTIONS - Rumpel C.; Kogel-Knabner I. (My University, 2002)
In many mine soils, lignite carbon is present as a potential carbon source for micro-organisms. Although the establishment of an active microbial community in reclaimed mine soils was recognised to be of great importance to reclamation success, the organic substrates available for micro-organisms have never been characterised in terms of bioavailability. The objective of this study was to examine if lignite in mine soils is decomposed and transformed during biodegradation. A chronosequence of lignite-rich mine substrates consisting of lignite-containing overburden material (parent substrate for soil development), a 14 years old mine soil and a 37 years old mine soil, both rich in lignite in addition to recent carbon were sampled and incubated for 16 months. Carbon mineralisation was monitored and the soil-respired CO2 subjected to 14C activity measurements. Additionally the 14C activity of humic acids extracted from the soils was determined. With the 14C activity data, lignite carbon contribution was estimated. These results show that lignite was decomposed in the lignite-containing parent substrate as well as in the 14 and 37 years old mine soil over the whole incubation period, the average decay rate of lignite being 0.025 and 0.007 g lignite C kg-1 C year-1. Lignite carbon was part of the humic acid fraction, indicating that lignite in the soil is oxidized during biodegradation A higher portion of lignite can be extracted as humic acids with increasing soil development. Thus, lignite in soil can be mineralised as well as humified and must be considered in the soil carbon cycle.